Location-Based Augmented Reality Information for Bus Route Planning System - Komang Candra Brata; Deron Liang; Sholeh Hadi Pramono (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Bus Route Planner applications will unfold their full potential when bus passengers are enabled to get information about the shortest path route, make a travel plan and get the correct buses in order to reduce the travel time. However, all these information are provided in text based and map view. It is difficult to understand them for the person who does not know place in the map. This paper describes the android base application of Augmented Reality (AR) that has feature to support the action of a bus user in an innovative and dynamic ways by putting additional information layer on smart phone camera screen and give the instruction assistant that leading the user way to the nearest bus stop. The experimental results show that, the overall functional of proposed application can be run well in various type of Android smart phone. When compared with similar bus traveling applications, the proposed application works more efficient.